National and European skills competitions – the experience of Cyprus - Małgorzata Kowalska; Maria Knais (Edukacja Ustawiczna Dorosłych)
Cyprus has restored its economy after the 2012–2013 financial crisis on many levels and reached the EU average life satisfaction in 2017. It has implemented the first phase of the National Health System (GESY), introduced a statutory minimum wage for all employees in all economic activities, and begun to reform the educational system. Noteworthy, the renewal of the collective agreements in the construction industry brought an end to a long-running dispute and strikes in the sector. The agreement restored working benefits and salary cuts imposed with the austerity measures in 2013. The industry needs skilled workers at the moment and the government of Cyprus recognizes the fact that skills are the passport to employment; the better skilled the individuals, the more employable they are. Good skills also tend to secure better-quality jobs and better earnings